Kinetic, Structural, and Mutational Analysis of Acyl-CoA Carboxylase From Thermobifida fusca YX - Shivaiah, Kiran-Kumar; Upton, Bryon; Nikolau, Basil J. (Frontiers in Molecular Biosciences, 2021)
Acyl-CoA carboxylases (AcCCase) are biotin-dependent enzymes that are capable of carboxylating more than one short chain acyl-CoA substrate. We have conducted structural and kinetic analyses of such an AcCCase from Thermobifida fusca YX, which exhibits promiscuity in carboxylating acetyl-CoA, propionyl-CoA and butyryl-CoA. The enzyme consists of two catalytic subunits (TfAcCCA and TfAcCCB) and a non-catalytic subunit, TfAcCCE, and is organized in quaternary structure with a A6B6E6 stoichiometry. Moreover, this holoenzyme structure appears to be primarily assembled from two A3 and a B6E6 subcomplexes. The role of the TfAcCCE subunit is to facilitate the assembly of the holoenzyme complex, and thereby activate catalysis. Based on prior studies of an AcCCase from Streptomyces coelicolor, we explored whether a conserved Asp residue in the TfAcCCB subunit may have a role in determining the substrate selectivity of these types of enzymes. Mutating this D427 residue resulted in alterations in the substrate specificity of the TfAcCCase, increasing proficiency for carboxylating acetyl-CoA, while decreasing carboxylation proficiency with propionyl-CoA and butyryl-CoA. Collectively these results suggest that residue D427 of AcCCB subunits is an important, but not sole determinant of the substrate specificity of AcCCase enzymes.